The Course of Tarsal Tunnel Syndrome after Ultrasound-Guided Injections. Issue 1 (January 2022) - Park, Joseph S.; Atesok, Kivanc; Pierce, Jennifer; Small, Benjamin; Perumal, Venkat; Cooper, M. Truitt
Category: Other; Ankle; Hindfoot; Midfoot/Forefoot; Sports Introduction/Purpose: Local ultrasound (US)-guided injections of anesthetics with corticosteroids are commonly performed for the conservative treatment of tarsal tunnel syndrome (TTS). This retrospective study aimed to investigate the course of TTS after US-guided injections. Methods: The study included patients who were diagnosed with TTS and received US-guided injections as their initial conservative treatment. The patients' pain levels were noted on a scale between zero and ten before and after each injection. The patients were divided into two groups: nonsurgical and surgical groups. The nonsurgical group included patients who had received US-guided injections and were not treated surgically, and the surgical group included those who received US-guided injections and ultimately underwent surgical tarsal tunnel release (TTR). The two groups were compared in terms of age, gender, post-injection follow-up time, and the amount of pain reduction immediately after injection (ΔPN). In the surgical group, the presence or absence of additional foot and ankle pathologies requiring operative treatment during TTR, and outcomes of surgical treatment were also assessed. Results: 218 patients were diagnosed with TTS and received US-guided injections as their initial treatment. After the injections, 169 patients (77.5%) required no TTR (nonsurgical group) and 49 patients (22.5%) underwent TTR (surgical group). The average ages for the nonsurgical and surgical groups were 53.8 and 48.9 years (P = 0.03). The average time between the injection and final follow-up for the nonsurgical group was 339 days. The average time between the injection and TTR for the surgical group was 145 days. There were no differences in pain relief after the injections between the nonsurgical and surgical groups (mean ΔPN: 3.6 and 3.8, respectively). In the surgical group, 16 patients (32%) presented with additional foot and ankle pathologies that were surgically treated during TTR. The average post-surgical follow up time was 117 days. At final follow up, 41 patients (84%) in the surgical group had no pain or functional impairment. Conclusion: US-guided injection can be an effective conservative treatment option for patients with TTS. Surgical release of tarsal tunnel may improve and resolve the overall symtoms of TTS in majority of the patients who do not respond to nonsurgical treatment. Younger age and additional foot and ankle pathologies appear to be associated with greater likelihood of undergoing TTR.